2006 38th North American Power Symposium 2006
DOI: 10.1109/naps.2006.359606
|View full text |Cite
|
Sign up to set email alerts
|

A Kalman Filter Approach to Quasi-Static State Estimation in Electric Power Systems

Abstract: equation based on physical laws. The Kalman filter [2] is a Abstract-Static state estimation in electric power systems is four-step algorithm that consist of the following: 1) Predicting normally accomplished without the use of time-history data. This the future state from inputs, 2) calculating the Kalman gain, 3) paper presents preliminary work on the use of the discrete-time correcting the prediction with new measurements, 4) updating Kalman filter to incorporate time history into the statee corring e predi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 10 publications
0
12
0
Order By: Relevance
“…Since power system is characterized by a quasi-static system which changes slowly and steadily, a transition relationship between consecutive states could be formulated and utilized in predefined algorithms to enhance the estimation results and predict the upcoming states as well [12]. In [14], a state transition matrix with identity matrix was formulated and the work was later extended using a diagonal matrix in [10].…”
Section: A Iekf Problem Formulationmentioning
confidence: 99%
See 2 more Smart Citations
“…Since power system is characterized by a quasi-static system which changes slowly and steadily, a transition relationship between consecutive states could be formulated and utilized in predefined algorithms to enhance the estimation results and predict the upcoming states as well [12]. In [14], a state transition matrix with identity matrix was formulated and the work was later extended using a diagonal matrix in [10].…”
Section: A Iekf Problem Formulationmentioning
confidence: 99%
“…This could be regarded as an optimization problem, whose solutions were computed by minimizing J as shown in (12), or equivalently in (13). (13) Note i refers to the standard deviation of the measurement covariance matrix such that: (14) This is an iterative problem that began with a flat start, i.e.…”
Section: Weighted Least Squares (Wls)mentioning
confidence: 99%
See 1 more Smart Citation
“…However, alternative estimation methods for DSSE in general have not been discussed extensively in research. In [8] and [9] the Kalman Filter method and the enhancement to Extended Kalman Filter (EKF) are proposed to incorporate time-history data in estimation problem. In [9] it is shown that the EKF methods leads to higher accuracy in estimation results compared to WLS and also improves convergence behaviour.…”
Section: Introductionmentioning
confidence: 99%
“…More recently, methods based on the use of the Kalman filter (KF) [15] have been proposed too. In particular, Blood et al [16] evaluated three different algorithms in order to study the performance of a pseudodynamic system, whereas in [17] they combined the basic power flow equations with the load forecast to create a discrete-time dynamic model for SE. Gelagaev [18] made a comparison between the WLS and the Extended Kalman Filter (EKF) methods and proposed a first analysis of the relative importance of process and measurement covariance matrices.…”
Section: Introductionmentioning
confidence: 99%